Effects on High School Students of the Use of Symbols that Show the Difficulty Level of a Problem - Iñaki Mugarra Soldevila; Joan Josep Solaz-Portolés; Carlos Caurín Alonso (Universidad Autónoma de Madrid, 2016)
In this paper we analyse the effect on the problem solving of the use of symbols that show the difficulty level of the problem (next to problem statement). Likewise, we study how students' academic level is involved in this effect. Sixty-seven High School students (10th or 12th grade students) have solved two problems, with two different difficulty levels, that have symbols that show the difficulty level (real or false). Moreover, four students have been interviewed to get information on their characteristics and the influence of the symbols. Results indicate that: a) the symbols have an influence on problem solving success, b) students' academic level does not change the effect of the symbols, and c) the symbols affect students with low self-efficacy and poor problem-solving strategies more than other students.